Комментарий удален
Комментарий удален
Комментарий удален

Ответы и объяснения

  • AlbuRin
  • светило науки
2013-07-24T09:59:52+04:00
№  9      V(2  -  V2)^2  +  V(V2  -  1)^2  =  2  -  V2  +  V2  -  1  =  1
               Ответ.      1.
№  19    ( (x  +  6)^3 (x  -  4) ) / (2  -  x)^5  >=  0
             1)  (x  +  6)^3  >=  0  ---->  x  >=  -6
                  (x  +  6)^3  <  0    ---->  x  <  -6
             2)  x  -  4  >=  0  ---->  x  >=  4
                  x  -  4  <  0    ----->  x  <  4
             3)  (2  -  x)^5    >=  0  ---->  x  <=  2 
                 (2  -  x)^5    <  0    ---->  x  >  2
А  теперь   на  числовой  прямой  методом  интервалов  найдём  решение.

                                                                     (x + 6)^3(x - 4)/(2 - x)^5  >=  0                +              -                       +                          -    -----------|---------------|------------------------------|-------------------- 
         -6              2                              4   
Ответ.    (-бесконечности;  -6 ]       Объединение        (2;   4]